(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Two coral reef monitoring sites were installed and assessed following SIMAC protocls at Isla Fuerte and Islas del Rosario, Caribbean coast fo Colombia. General cover of algae and corals were similar in all the plots. Disease and bleaching percentages were low (< 7 %), with the exception of the site La Coca where disease occurence was high (14.57 ± 3.81 and 17.04 ± 2.17 %). Mobile invertebrates of commercial or ecological importance were scarce. A total number of 46 of 76 fish species were registered, higlighting the abundance of commercial families such as Serranidae and Lutjanidae in La Coca. The continuity of the monitoring program and the installation of new sites will provide tools to improve local mangement strategies and to progressively understand the long-term dynamics of coral reefs in Colombia.